The correllation between incidence rate of pertussis and vaccination rate of children from 1998 to 2016 in Poland - Jakub Czarnota; Tomasz Skubel; Michał Dobrzyński; Dorota Sokół; Arkadiusz Standyło; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2019)
Introduction and purpose: Pertussis is becoming a more and more common problem among polish children and youth. In the group of newborns and infants the pertussis course can be severe and lead to serious complications even including death from the disease (~1%